2017
DOI: 10.1017/s0030605317001211
|View full text |Cite
|
Sign up to set email alerts
|

Does forest management and researchers’ presence reduce hunting and forest exploitation by local communities in Tsitongambarika, south-east Madagascar?

Abstract: Hunting of wildlife is one of the major threats to biodiversity. For effective conservation programmes in countries where hunting and shifting agriculture are the main sources of subsistence, forest management should aim to reduce hunting pressure and forest exploitation. The presence of researchers has been promoted as one of the main ways to mitigate anthropogenic pressures on wildlife populations. Our aim was to test whether local management and the establishment of a research station had a role in decreasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Also, maintaining permanent presence at field sites may reduce local anthropogenic pressures (e.g., hunting, timber harvesting) on species' populations as a consequence of providing consistent employment/direct benefits to local communities (Campera et al, 2019; Wrangham & Ross, 2008; Wright et al, 2012). Regardless of whether or not PAs are a legitimate predictor of species occurrence, a greater effort is needed to maintain park boundaries.…”
Section: Discussionmentioning
confidence: 99%
“…Also, maintaining permanent presence at field sites may reduce local anthropogenic pressures (e.g., hunting, timber harvesting) on species' populations as a consequence of providing consistent employment/direct benefits to local communities (Campera et al, 2019; Wrangham & Ross, 2008; Wright et al, 2012). Regardless of whether or not PAs are a legitimate predictor of species occurrence, a greater effort is needed to maintain park boundaries.…”
Section: Discussionmentioning
confidence: 99%
“…Although lemur species are well known for their ecological, physiological and behavioural flexibility, we found that their abundance was generally higher at lower elevations. Given the limited extent of undisturbed lowland rainforests in Madagascar, it is pivotal to promote conservation measures to maintain this habitat that hosts high abundances of several lemur species (Kremen et al 1999, Campera et al 2017. Rapid habitat degradation is occurring elsewhere in lowland rainforests (Myers et al 2000, Gibson et al 2011, so a similar analysis could be extended to other regions of the world where endemic taxa occur at different elevations, to determine their ability to occupy elevation gradients.…”
Section: Discussionmentioning
confidence: 99%
“…Field sites that experience less human traffic may be better for the primates themselves because the populations experience less exposure to human researchers and potentially less attraction for the area by tourists, students, and short‐term researchers. Studies at newly founded field sites also provide new information on geographic variation and may afford a new conservation value to the area . Lack of infrastructure, inconsistent funding, and inconsistent local community support may, however, make research and conservation challenging at these relatively unstudied sites.…”
Section: Moving Forwardmentioning
confidence: 99%